Failure of daratumumab in the treatment of anti-synthetase syndrome: A case report - Nam Nguyen; Valérie Leclair; Rayan Kaedbey; Marie Hudson (SAGE Open Medical Case Reports)
Anti-synthetase syndrome is a subset of idiopathic inflammatory myopathies, for which refractory disease can be difficult to treat. Daratumumab, an anti-CD38 monoclonal antibody primarily used in hematologic malignancies, has recently shown promise in very few case reports of refractory idiopathic inflammatory myopathies. We present a case of a 44-year-old man with anti-Jo1 anti-synthetase syndrome with concurrent anti-Ro52, in which myositis remained refractory to multiple immunosuppressants. Despite treatment with daratumumab, the patient did not respond and ultimately succumbed to infection. This case underscores the need for further research to better define the role of daratumumab in idiopathic inflammatory myopathies and identify predictors of treatment response.